Specifics of perception of images of professions in advertising and public relations - K. A. Arzhanova; G. V. Dovzhik (Вестник университета)
The article сonsiders the peculiarities of perception of public relations and advertising specialists ‘ images by future representatives of these professions. The paper presents the results of a study to identify the Delta perception of images of specialties from students in the field of “Public Relations and Advertising”. For the cumulative assessment of image perception, the method of private semantic differential was applied, using the original scale of perception of the above-mentioned professions developed by the authors. As a result of the research, the distribution profiles of the average values of independent variables were analysed and the specifics of the perception of specialties was revealed. The obtained data can be used to correct these images, as well as formulate recommendations for their improvement.